Performance Audit of National Rural Health Mission (NRHM) in Uttarakhand (2005-2008) - CAG of India (CAG of India, 2009)
Performance review of the National Rural Health Mission (NRHM) activities in Uttarakhand for the period 2005-08 brought out several positives like introduction of ‘Dial-108’ emergency ambulance service, which has got overwhelming response from the public. In maternal and child health care, there was a marginal increase in institutional deliveries. ‘ASHA-Plus’ scheme introduced in two districts, is a unique feature run with NGO collaboration. The cure rate targeted for tuberculosis and cataract operations was achieved in all the three years, while the State has brought down the leprosy prevalence rate in the year 2005 itself. However, there were major areas of concern requiring corrective measures as brought out below: The objective of decentralized planning with community participation was not achieved. The community was not involved in any aspect of health care system neither in planning nor in implementation and monitoring. Block and village plans, which were to form the basis for district plans, were not prepared. District health authorities did not own up the district level plans prepared with outside support. Baseline survey of availability of services at various levels of heath care system was incomplete. Household survey was not conducted. Convergence with other departments in implementation of the programme was also ineffective. The Village Health and Sanitation Committees (VHSC) at villages and Rogi Kalyan Samitis (RKS) at PHCs were not formed and public hearings (Jan Sunwai) were not conducted. NRHM envisaged streamlining the fund flow for health care services and improving coordination by merging all the existing societies and providing a single window for all the Mission activities. However, independent societies are functioning for disease control programmes in the State. Although the State has increased the expenditure on health in all the three years, it failed to contribute its share of 15 per cent to NRHM kitty in the year 2007-08. Fund releases to the districts were not proportionate to the population of the district and the State was unable to absorb the increased funding. 35 per cent of the funds remained unutilized even as the infrastructure in the health centres remained inadequate. Basic records of accounts were not maintained properly either at the State or the district level. Infrastructure creation/up-gradation- both physical and human, is an area where the State fared poorly in achieving the targets set by the Mission. In the absence of critical equipment in Operation Theatres and diagnostic and laboratory services, the viability of upgrading CHCs as the First Referral Unit (FRU) remained questionable and the provision of reliable and quality health service at an affordable cost remained unfulfilled. This also resulted in low bed occupancy at the PHCs and CHCs, thus shifting the burden to district hospitals. Mobile Medical Units (MMU) were not purchased despite availability of funds. Severe shortage of skilled manpower and skewed deployment of the available manpower appears to cripple health infrastructure in the State. Delay in completion of construction of health centres led to cost overrun. Centralized purchase of drugs, not linked to field level requirements, led to several anomalies. In all the sampled districts, the ANMs/ Pharmacists were distributed Schedule H drugs, which are to be issued only on the prescription of Registered Medical Practitioners. Expired ORS sachets were dumped in large quantities in the backyard of the State Health Society building. RCH was plagued with considerable over-reporting in achievements especially in immunization and distribution of Iron Folic Acid (IFA) tablets among expectant mothers. 55 per cent of women in the State are reported to be anaemic and 300 women in every one lakh pregnancies die in labour in the State. In the three sampled districts, the stock of IFA tablets was sufficient to cover only 3.4 per cent of the registered pregnant women but the number reported was 25 times the actual. Janani Suraksha Yojana, meant to incentivize women to opt for institutional delivery through payment at the time of discharge from the hospital, could not ensure that payments were released to the beneficiaries on time, despite availability of funds. The beneficiary-survey revealed that awareness of NRHM and benefits flowing through it were confined to a small section of the society, indicating ineffective coverage of IEC activities. Visits by the ANMs to the villages were not being undertaken at the prescribed intervals due to excess workload and topographical conditions of the areas and large population coverage. There were delays in payment to ASHAs and lack of facilities in the sub district health centres and distance factor forced the beneficiaries to prefer home deliveries. Availability of medicines through the hospitals was inadequate and the beneficiaries had to partially pay for the medicines on each visit. Lack of coordination among AWW, ASHA and ANMs was also noticeable in some areas. Training to school teachers regarding NRHM is yet to be imparted. The findings of the performance audit indicate that the Mission goal of providing affordable, accountable, effective and reliable healthcare facilities is not moving at the desired pace. The State Government needs to initiate adequate measures and take appropriate corrective action expeditiously to ensure that the objectives of the Mission are achieved by the end of the Mission period (2012).
For the Period 2005-2008